การพัฒนาแนวทางการบริหารการฝึกประสบการณ์วิชาชีพของนักศึกษาพยาบาลระดับอุดมศึกษในภาคตะวันออกเฉียงเหนือ - บนขุนทด, ปัณณทัต; ยุระชัย, สำเร็จ; พรหมมีเนตร, ไพโรจน์; ผกามาศ , พงษ์ศักดิ์ (Journal of Graduate MCU KhonKaen Campus, 2018)
การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาปัญหาและแนวทางการบริหารการฝึกประสบการณ์วิชาชีพของนักศึกษาพยาบาลระดับอุดมศึกษาในภาคตะวันออกเฉียงเหนือใน 5 ด้านคือ ด้านส่วนตัวของนักศึกษา ด้านการเรียนการสอนในคลินิก ด้านอาจารย์นิเทศ ด้านแหล่งฝึกประสบการณ์วิชาชีพและด้านสวัสดิการของสถาบัน กลุ่มตัวอย่างประกอบด้วย นักศึกษาพยาบาลและอาจารย์นิเทศ จำนวน 306 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม มีค่าดัชนีความสอดคล้อง (IOC) ระหว่าง 0.80-1.00 และหาความเที่ยงโดยใช้วิธีสัมประสิทธิ์แอลฟ่าของครอนบาค (Cronbach’ s Coefficient of Alpha) เท่ากับ 0.92 วิเคราะห์ข้อมูลเชิงคุณภาพ โดยการตีความสร้างข้อสรุป ส่วนข้อมูลเชิงปริมาณ วิเคราะห์ข้อมูลโดยใช้คอมพิวเตอร์โปรแกรมสำเร็จรูป สถิติที่ใช้ในการวิจัยได้แก่ ค่ามัธยฐาน (Median) และค่าพิสัยระหว่างคลอไทล์ (Inter Quartile Range) ความถี่ (Frequency) ค่าร้อยละ (Percentage) ค่าเฉลี่ย (Mean : ) และส่วนเบี่ยงเบนมาตรฐาน (Standard Deviation : S.D.) ผลการวิจัยพบว่า ปัญหาในการบริหารการฝึกประสบการณ์วิชาชีพของนักศึกษาพยาบาล ด้านส่วนตัวของนักศึกษาอยู่ในระดับมาก ด้านการเรียนการสอนในคลินิกอยู่ในระดับปานกลาง ด้านอาจารย์นิเทศอยู่ในระดับน้อย ด้านแหล่งฝึกประสบการณ์วิชาชีพอยู่ในระดับปานกลาง ด้านสวัสดิการของสถาบันอยู่ในระดับปานกลางและภาพรวมอยู่ในระดับปานกลาง และแนวทางในการบริหารการฝึกประสบการณ์วิชาชีพของนักศึกษาพยาบาล ด้านส่วนตัวของนักศึกษาได้แก่ ต้องปลูกฝังความรักต่อวิชาชีพพยาบาลให้กับนักศึกษาเมื่อเริ่มเข้าเป็นนักศึกษาพยาบาลและควรต้องมีการคัดเลือกนักศึกษาที่ชอบวิชาการพยาบาล พร้อมกับจัดให้นักศึกษาได้มีเวลาพบปะสังสรรค์แลกเปลี่ยนความคิดเห็นต่อกันในการเข้ารับการฝึกประสบการณ์วิชาชีพพยาบาล ด้านการเรียนการสอนในคลินิกได้แก่ ต้องจัดให้มีการปฐมนิเทศและกำหนดวัตถุประสงค์ พร้อมกับวางแผนในการเรียนการสอน มอบหมายงานในการฝึกประสบการณ์วิชาชีพให้กับนักศึกษาตามความรู้ความสามารถและควรทำความเข้าใจและวิธีการเรียนการสอนในการฝึกประสบการณ์วิชาชีพด้วย ด้านอาจารย์นิเทศได้แก่ แจ้งวัตถุประสงค์และแผนการสอนต่ออาจารย์นิเทศและให้อาจารย์นิเทศศึกษาหลักสูตรการเรียนการสอนก่อนออกปฏิบัติงานกับนักศึกษา พร้อมกับจัดปฐมนิเทศอาจารย์ก่อนที่จะร่วมออกปฏิบัติงานกับนักศึกษา ด้านแหล่งฝึกประสบการณ์วิชาชีพได้แก่ จัดแหล่งฝึกประสบการณ์วิชาชีพให้เหมาะสมกับนักศึกษาและตรงตามวิชาที่จะต้องฝึกปฏิบัติ ให้ความสำคัญและความเชื่อมั่นต่อนักศึกษาในการให้การพยาบาลที่แหล่งฝึก ประสบการณ์วิชาชีพ พร้อมกับให้มีค่าตอบแทนอย่างเหมาะสมกับการฝึกปฏิบัติงานกับแหล่งฝึกประสบการณ์วิชาชีพและด้านสวัสดิการของสถาบันได้แก่ ขอให้มีการจัดรถรับ-ส่งให้กับนักศึกษาอย่างเพียงพอหรือประสานงานในการจัดที่พักให้เหมาะสมและพอดีกับจำนวนนักศึกษา พร้อมกับให้มีบริการอาหารแก่นักศึกษาในช่วงเวลาที่ฝึกปฏิบัติ The objective of this research was to study the problems and the guidelines development of the training internship management for the undergraduates nursing students in the Northeast of the 5 aspects of the student’s. The teaching in the clinic, the supervising faculty, the field experience and the welfare of the institution. The sample consisted of 306 nursing students and faculty supervision were used in this study was a questionnaire. Consistency indices (IOC) between 0.80 - 1.00 and find out by using coefficient Cronbach’s alpha was 0.92, analysis of qualitative data. Created by interpreting the conclusions. The data were analyzed by the computer program. The statistics used in the research include the median and range between the chlorinated tile. (Inter-Quartile Range) Frequency, Percentage, Average and standard deviation (S.D.). The research findings were as follows: Problems in the management of professional experiences of nursing students. The students’ personal, the level. The teaching in the clinic, in the medium. The supervising faculty, at a low level. The field experience, in the medium. Welfare institutions, in the medium and snapshots, in the medium. And the guidelines development of the training internship management for the undergraduates nursing students. Including the students' personal to instill a love of nursing to students when starting a nursing student and should be subject to qualifying students like nursing. And to arrange for students to have time to socialize and exchange ideas and experiences in the nursing profession. The teaching in the clinical area. Must provide orientation and objectives. And to plan instruction. Assigned the task of training experience to students as appropriate. Knowledge and understanding and the teaching practice of professional experience. Faculty supervision, including the notify objectives and lesson plans, teacher supervision and supervisory faculty teaching courses before working with students. With an orientation prior to joining the faculty work with students. Including the field experience. The field experience to suit the students and meet the subjects to practice on. Focus and confidence to students in the nursing field experience. Along with providing compensation appropriately to practice with field experience and the welfare of the institution, including. Have a car-send to a student or adequate coordination arrangements. Accommodation to suit and fit the student. Along with providing food to students during the practice sessions.